Sounding Beckett: a practitioner’s perspective - Eadie, Jimmy (My University, 2023)
This article discusses theatre sound design through the lens of a practitioner-researcher. What follows is a reflection on the process, context and significance of this practice within theatre arts. Initially touching on some of the terminology and theory behind the development of this discipline, the discussion will focus on the application of design methods and strategies to three radio adaptations of Samuel Beckett’s works: All that Fall (1957), Embers (1959) and Cascando 1963). The aim of this critique is to broaden the discussion on theatrical sound design by analysing specific works and design strategies from my own experience as a practitioner engaging with these three seminal Beckett works. This article argues that theatre sound design is an intermedial, holistic process that can reinforce or counterpoint a specific mood or atmosphere, reveal performance characteristics and, most importantly, contribute to the advancement of the storytelling, which is at the heart of most theatre productions.
PUBLISHED